Trade Costs of Pakistan with its Major Trading Partners: Measurement and its Determinants - Zafar Mahmood†; Saba Altaf; Shabana Noureen (NUST Journal of Social Sciences and Humanities, 2021)
Trade costs are cited as an important determinant of volume of trade. Higher trade cost is an obstacle to trade as it impedes the realization of gains from trade liberalisation. Determinants of trade costs of Pakistan for the period 2003-2012 with their major trading partners across Asia, European Union and North America are investigated. Several gravity type variables have been used as trade cost determinants. Trade costs for agricultural and non-agricultural sector are also calculated using a micro-founded trade costs measure. Estimates of trade costs equivalents show a declining trend of trade costs estimates over the period of study. Fully Modified Ordinary Least Square estimation of the model shows that tariff rates and distances between the trading partners increase the bilateral trade costs and thus adversely affect trade. Results show that improvements in port infrastructure and membership of free trade agreement significantly reduce the trade costs. Z-test shows that the effect of determinants of trade costs for agricultural and non-agricultural sectors is invariant. This paper recommends that the agreement on trade facilitation be implemented and reduce the red tape at border crossings to cut down the trade costs.